Stereotactic low voltage x-ray radiotherapy for treating neovascular age-related macular degeneration. (June 2014) - Chakravarthy, Usha; Czeszynski, Alan
Abstract : Neovascular age-related macular degeneration (nvAMD) is a sight-impairing condition managed by the intraocular administration of inhibitors of VEGF, which include ranibizumab, bevacizumab and aflibercept. Because the effects of these biologicals wear off, the treatment has to be repeated as often as monthly. The disease is chronic and it is known that a proportion of patients continue to receive treatment for 5 years or more thus there are inherent burdens to the patient, provider and payer. Radiotherapy is adjunctive to anti-VEGF therapy in the control of nvAMD. There is a known synergistic effect of radiation and angiogenesis inhibitors. Radiotherapy as delivered by the Oraya IRay system is intended as a one-time therapy for the treatment of nvAMD, which has been shown to reduce the need for anti-VEGF by 32% over one year in a broad cohort of previously treated patients, and up to 55% for a well-defined subgroup. The Oraya Therapy offers an option to preserve vision while reducing the need for continuous clinic visits for monitoring and treatment.